PEMEROLEHAN BAHASA ANAK USIA 3-4 TAHUN DI DESA TEGALREJO BANYUWANGI DALAM KAJIAN PSIKOLINGUISTIK - Ali Manshur; Rikha Nahrul Jannah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research will discuss the form of language acquisition for children aged 3-4 years and what factors influence language acquisition in children aged 3-4 years. In this case the researcher studies in the realm of psycholinguistics, because the language process in children is inseparable from psychology in humans. This research uses descriptive qualitative type. Retrieval of data using observation, interviews, and documentation techniques. The object of this study was children aged 3-4 years. Data Analisys from this reseach is The use of data analisys model interaktif according from Milles and Huberman is data collectif, data reducsi, data presentation, adn conclusion. The results and conclusions of this study are that 3-year-old children are able to communicate with their interlocutors using simple sentences. Consonantal pronunciation /r/ and consonant groups are not yet mastered. Children who are 3.5 years old can say declarative, introgative sentences. Mastery of several objects around him can he express through storytelling. Consonantal pronunciation /r/ and consonant groups are not yet mastered. Children aged 4 years have increased language production. Language acquisition factors for children aged 3-4 years are biological, environmental, cognitive, and electronic media that are often accessed such as devices and television.